Proceedings of the 2013 International Conference on Applied Social Science Research (ICASSR-2013) 2013
DOI: 10.2991/icassr.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Returns to Education of Persons with Disabilities in Rural China

Abstract: -The aim of this paper is to estimate the returns to education in the disable people in rural China in the past 20 years. The regression of Mincerian wage equation as the method is used, and the data is based on CHNS data in 1991-2009 survey. The results show that the education level has significant positive linear relationship with the rate of returns to education (RRE). The RRE for the rural disable people is lower than the RRE of the disabled in urban, which are 5.3% and 7.6%. The RRE of male disabled is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The progress of implementing the UNCRPD is slow, evidenced by the delayed country report on its domestication, unavailability of statistical data on the prevalence of persons with a disability, lack of data monitoring tools, and differences in understanding of what needs to be done. This appears to correspond well to the results presented in other studies [2,29,47,49]. Besides, selective implementation of the UNCRPD has resulted in a lack of quantifiable impact on the effectiveness of the interventions employed [39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The progress of implementing the UNCRPD is slow, evidenced by the delayed country report on its domestication, unavailability of statistical data on the prevalence of persons with a disability, lack of data monitoring tools, and differences in understanding of what needs to be done. This appears to correspond well to the results presented in other studies [2,29,47,49]. Besides, selective implementation of the UNCRPD has resulted in a lack of quantifiable impact on the effectiveness of the interventions employed [39].…”
Section: Discussionsupporting
confidence: 91%
“…For example, the government provides a monthly disability pension grant that the persons with disabilities have complained to be too little to protect livelihoods or to be used as collateral security to access mainstream microfinance as documented in some studies [45,46]. Evidence of entrepreneurship opportunities noted was limited to educated and employed persons with disabilities, hence the call for support in the inclusivity of persons with disabilities in education [8,47]. Each additional year of schooling for persons with disabilities will improve opportunities to compete in entrepreneurship, and other markets were noted with decent wages, as indicated in studies done in China [48].…”
Section: Discussionmentioning
confidence: 99%
“…(2) it releases other household members from caring responsibilities, allowing them to engage in employment and other productive activities; and (3) it increases children's potential productivity and wealth creation, which in turn helps to alleviate poverty [16][17][18].…”
Section: The Right To Inclusive Education and Carementioning
confidence: 99%
“…This evidence highlights the importance of starting inclusive initiatives as early as possible, along with strengthening learning and participatory processes. LeRoy and Simpson (1996 [122]) found that primary students without disabilities in inclusive settings in Michigan, United States, were more positive and interactive with their peers with disabilities than secondary-age students. 80% of elementary students indicated that they appreciated students with disabilities in their classrooms, between 90%-100% that they talked and played routinely with them, and between 65% and 70% that they spent free time with them and considered them friends (LeRoy and Simpson, 1996 [122]).…”
Section: Socialisationmentioning
confidence: 99%
“…LeRoy and Simpson (1996 [122]) found that primary students without disabilities in inclusive settings in Michigan, United States, were more positive and interactive with their peers with disabilities than secondary-age students. 80% of elementary students indicated that they appreciated students with disabilities in their classrooms, between 90%-100% that they talked and played routinely with them, and between 65% and 70% that they spent free time with them and considered them friends (LeRoy and Simpson, 1996 [122]). A recent review by Kart and Kart (2021 [116]) found that students without SEN have socially benefited from being in inclusive classrooms with students with SEN, in particular in terms of reduction of fear, hostility, prejudice, and discrimination as well as increase of tolerance, acceptance, and understanding.…”
Section: Socialisationmentioning
confidence: 99%